Application of fresh frozen plasma transfusion in the management of excessive warfarin-associated anticoagulation. Issue 2 (April 2022) - Luo, Yuanyuan; Ma, Chunya; Yu, Yang
Abstract : Abstract: Warfarin is a commonly used oral anticoagulant. Patients with artificial valve replacement, atrial fibrillation, pulmonary embolism, deep vein thrombosis, and other diseases require long-term anticoagulant oral treatment with warfarin. As warfarin exhibits prompt action with long maintenance time, it has become a key drug for the treatment of patients at risk of developing thrombosis or thromboembolism. Warfarin is a bican coumarin anticoagulant, that exhibits competitive action against vitamin K as its mechanism of action, thereby inhibiting the synthesis of coagulation factors—predominantly the vitamin K-dependent coagulation factors II, VII, IX, and X—in hepatocytes. Long-term warfarin is known to significantly increase the risk of organ bleeding in some patients, while some patients may need to reverse the anticoagulation effect. For instance, patients scheduled for emergency or invasive surgery may require rapid anticoagulation reversal. During such medical circumstances, fresh frozen plasma (FFP) is clinically used for the reversal of excess warfarin-associated anticoagulation, as it contains all the coagulation factors that can alleviate the abnormal blood anticoagulation status in such patients. Accordingly, this article aims to perform an in-depth review of relevant literature on the reversal of warfarin with FFP, and insightful deliberation of the application and efficacy of this clinical intervention.